Effects of invasive clam (Corbicula fluminea) die-offs on the structure and functioning of freshwater ecosystems - Novais, Adriana (2017)
1. Freshwater ecosystems are highly susceptible to the impacts of global climate change, including extreme events such as floods and droughts. These impacts may be influenced by the presence of widespread invasive alien species, such as the Asian clam Corbicula fluminea (Cyrenidae). 2. The high density and biomass attained by C. fluminea in the Minho River (NW Iberian Peninsula) are responsible for several ecological impacts. By using a manipulative experiment under natural conditions, we assessed the effects of C. fluminea die-offs on the structure of microbial (fungi and bacteria) and invertebrate communities and leaf-litter breakdown. 3. Results suggested that C. fluminea die-offs did not affect the structure of microbial and invertebrate communities nor litter breakdown rate. However, differences in temporal dynamics were detected and followed an ecological succession during the experiment. 4. Our study revealed that the presence of live C. fluminea stimulated fungal biomass and leaf mass loss, probably due to an increased availability of nutrients via production of faeces and pseudofaeces.